Displaced The Human Cost of Development and Resettlement - Bennett, O. (Palgrave Studies in Oral History, 2012)
A collection of oral histories that reveal the loss of cultural continuity, identity, shifts in family responsibilities, gender roles and fractured relationships between generations that are just some of the challenges people face as they attempt to rebuild lives and communities.